Molecular Studies and Possible Relatedness Between R Plasmids from Groups B and D Streptococci - El-Solh, Névine (1978)
Resistance plasmids isolated from Streptococcus agalactiae (group B) and S. faecalis (group D) have been compared in regard to resistance markers, molecular weight, and DNA-DNA homology. Three of them (pIP501, pIP612, and pIP613) have been found to confer identical (or very similar) resistance patterns (erythromycin, lincomycin, and streptogramin B, respectively) and to have similar molecular weights (19.8 × 10(6), 22.7 × 10(6), and 17.6 × 10(6), respectively) and a high level of DNA-DNA homology in hybridization experiments (90 to 100%). These results are compatible with the view that these plasmids may derive from one common ancestor, and/or that they can be transferred between unrelated Streptococcus strains belonging to the same or different groups.